Uncertainty in aiming movements and its association to hand function - Flávia Priscila de Paiva Silva; Sandra Maria Sbeghen Ferreira de Freitas; Emelli da Silva Comenalle; Sandra Regina Alouche (Motriz: Revista de Educacao Fisica, 2015)
AbstractThe purpose of this study was to analyze the influence of the uncertainty of target location on the planning and execution of aiming movements performed towards the ipsilateral and contralateral directions by the right and left upper limbs. In addition, the association between the performance of aiming movements and the performance of functional manual tasks was investigated. Two tasks were proposed: with prior knowledge of the movement direction (simple reaction time) or not (choice reaction time). The grip strength and manual dexterity were measured. The choice option in response (i.e. uncertainty) influenced planning of the aiming movements, but not its execution, while movements performed towards the contralateral direction were worse in execution as compared to the ipsilateral direction. Manual dexterity was significantly correlated with reaction times, while the performance during movement execution was significantly correlated with handgrip/pinch strength.